Pemphigus vulgaris: a review of 12 cases - Ana Carolina Vasconcelos; Sergio Augusto Miguens Jr; Maria Antonia Figueiredo; Fernanda Gonçalves Salum; Karen Cherubini (Editorial Ciencias Médicas, 2015)
Introduction: pemphigus vulgaris is an autoimmune mucocutaneous disease, which presents at clinical examination as blisters, erosions and ulcerations of the skin and mucous membranes. Objective: the aim of this study was to review 12 cases of pemphigus vulgaris diagnosed at the Stomatology Department of São Lucas Hospital, Pontifical Catholic University of Rio Grande do Sul. Methods: the medical charts were analyzed considering patients age and sex; anatomic site and clinical aspect of the lesions; as well as symptoms, duration and clinical course of the disease. Results: the mean age of the patients was 46.7 years; most of cases occurred in females (75.0 %); buccal mucosa was the site most frequently affected (83.3 %), and 25 % of cases showed extraoral manifestations. Erosion/ulceration was the most prevalent clinical appearance (83.3 %), and pain occurred in 100% of cases. The mean time of development of the lesions reported by the time of the diagnosis was 12.3 months, and the mean time of follow-up was 2 years. All patients received systemic therapy with prednisone, meanwhile in 58.3 % of cases it was associated with topic therapy and in 25 %, with systemic immunosuppressive therapy. One case (8.3 %) remained in remission regardless of the treatment withdrawal. Conclusion: Pemphigus vulgaris is a disease with important morbidity, which requires the attention of the dentist as a way to achieve early diagnosis.